2018
DOI: 10.7150/ijbs.22896
|View full text |Cite
|
Sign up to set email alerts
|

The Role of G Protein-coupled Receptor Kinases in Cancer

Abstract: G protein-coupled receptors (GPCRs) are the largest family of plasma membrane receptors. Emerging evidence demonstrates that signaling through GPCRs affects numerous aspects of cancer biology such as vascular remolding, invasion, and migration. Therefore, development of GPCR-targeted drugs could provide a new therapeutic strategy to treating a variety of cancers. G protein-coupled receptor kinases (GRKs) modulate GPCR signaling by interacting with the ligand-activated GPCR and phosphorylating its intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 152 publications
0
41
0
1
Order By: Relevance
“…GRKs participate in a wide range of cellular physiological and pathological activities and there are increasing evidences indicated that some of which are closely related to the occurrence and progression of tumors [5][6][7] . In the present study, we reported that absent expression of GRK4 in tumors was significantly associated with worse outcomes in patients with HCC (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GRKs participate in a wide range of cellular physiological and pathological activities and there are increasing evidences indicated that some of which are closely related to the occurrence and progression of tumors [5][6][7] . In the present study, we reported that absent expression of GRK4 in tumors was significantly associated with worse outcomes in patients with HCC (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern and function of the GRK family members have been reported differed among various tumors [6,7,24,25] . In HCC, GRK3 was expressed in larger tumors and early-stage diseases, whereas GRK6 was prone to expression in smaller, moderate histological grade and metastatic tumors [9,10] .…”
Section: Grk4 Was Found Frequently Mutated In High Microsatellite Insmentioning
confidence: 99%
See 1 more Smart Citation
“…GPCRs scaffold many intracellular signaling proteins by different signaling pathways and induce signaling cascades independent of G protein activation—including Wnt, Notch, transforming growth factor-β (TGF-β), and the hedgehog (Hh) pathways—as well as downstream kinases—such as phosphoinositide 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) [ 6 ]. Additionally, activated GPCRs also interact with GRKs or other receptors, mediating the downstream signal pathway [ 7 ].…”
Section: Structure and Signal Transduction Of G Protein-coupled Rementioning
confidence: 99%
“…GRKs and barrestins may directly affect functioning of non-GPCRs or indirectly regulate non-GPCR signaling. In addition, incoming evidence supports that changes in function and/or expression of GRKs and barrestins may be important in cardiovascular, inflammatory, metabolic, or cancer pathologies (Vroon et al, 2006;Schumacher and Koch, 2017;Steury et al, 2018;Yu et al, 2018). A better understanding of the pathological roles of GRKs and b-arrestins would provide a basis for new therapeutic targets in different human diseases.…”
mentioning
confidence: 98%